Effect of different levels and sizes of walnut seed residues on phosphorus availability and alkaline phosphatase activity in calcareous soil - Sakar Abdulqadr Saheed; Shakar Jamal aweez; Snowber Muhamad Ahmed (مجلة بغداد للعلوم)
A laboratory experiment has been carried out in the College of Science-University of Salahaddin to study the effect of different levels (0,5,10 and 15%) and sizes(250 and 1000µm) of walnut seeds residues and (160mg.kg-1) phosphorus fertilization on the concentration of phosphorus availability and alkaline phosphatase activity in calcareous soil during 15 and 30 days period of incubation, the experimental design in factorial complet randomize design (C.R.D) with three replications. The results indicated that the application of different levels of walnut seed residues decreases the concentration of phosphorus availability and alkaline phosphatase activity, however the results revealed that combination between levels and sizes of sieved walnut seed residues and phosphorus fertilizer significantly (p≤0.05) affected the alkaline phosphatase activity and the concentration of available phosphorus, the highest values (29.633 µgPNPg-1.hr-1and 6.442mg.kg-1) have been recorded in treatments combination received 1000µm, 15% walnut seed residues and phosphorus fertilizer, respectively.